Adolescent-Mother Communication, Self-Control and Internet Use as Predictors of Psychological Well-Being among Indonesian Adolescents - Pramesti, Yustia; Yuliaty, Lilik Noor; Riany, Yulina Eva (Journal of Educational, Health and Community Psychology, 2025)
Previous studies have found that problematic internet use (PIU) among teenagers may lead to anxiety, fear of missing out (FOMO), and social withdrawal, all of which can negatively impact their psychological well-being. However, limited research has explored the combined role of adolescent–mother communication and self-control as protective factors in this relationship, particularly in the Indonesian adolescent population. This study aims to examine the influence of adolescent–mother communication, self-control, and PIU on the psychological well-being of adolescents. The research was conducted in South Tangerang City using a random sampling technique, involving 321 junior and senior high school students. Participants were adolescents aged 13–18 years who lived with their biological parents and reported using the internet for more than six hours per day. The instruments used included the Parent–Adolescent Communication Scale by Barnes and Olson, the Brief Self-Control Scale by Tangney, the Problematic Internet Use Scale by Boubeta et al., and the Short Version of the Psychological Well-Being Scale by Ryff. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS version 3.0. The findings revealed the following: (1) Adolescent–mother communication in the "openness" dimension had a direct, significant, negative effect on problematic internet use. (2) Communication in the "problems" dimension did not have a direct effect on PIU but had an indirect effect mediated by self-control. (3) Problematic internet use had a direct, significant, negative impact on adolescents’ psychological well-being. These results underscore the crucial role of adolescent–mother communication and self-control in mitigating the negative impact of problematic internet use on adolescent psychological well-being.